Estudiantes Del Título Superior De Música De Viento Madera. Relación Entre Los Niveles Motivacionales Y El Optimismo Disposicional - Zarza-Alzugaray, Francisco Javier (European Scientific Journal, ESJ, 2018)
The motivation and the dispositional optimism are two constructs that in the population of musicians in training have not yet been taken into account in order to their scientific study. However, we present an approach to the problem, adapting it to the musical contexts, based on the motivational model proposed by Manassero and Vázquez (1998); the motivational factors are the interest, effort, perfectionism, the specific demands of the task and the exams. At the same time, taking as valid the approach to the model of optimism from Carver, Scheier and Segerstrom (2010), in which the optimistic tendency is defined as a belief that each person has in his life towards the experience good experiences, significant relationships have been found between the different motivational factors and optimism; at the same time and with regression techniques it has been possible to explain 29.4% of the variance of the general factor of optimism with only the significant presence in the model of the specific factor of the task. In this sense, more research is needed to increase the knowledge of both constructs for the improvement of pedagogical practice in higher musical training centers.